2009
DOI: 10.1099/ijs.0.004267-0
|View full text |Cite
|
Sign up to set email alerts
|

Croceicoccus marinus gen. nov., sp. nov., a yellow-pigmented bacterium from deep-sea sediment, and emended description of the family Erythrobacteraceae

Abstract: Croceicoccus marinus gen. nov., sp. nov., a yellow-pigmented bacterium from deep-sea sediment, and emended description of the family Erythrobacteraceae A Gram-negative, aerobic, neutrophilic, coccoid bacterium, strain E4A9 T , was isolated from a deep-sea sediment sample collected from the East Pacific polymetallic nodule region. 16S rRNA gene sequence analysis showed that the isolate was related to the type strain of Altererythrobacter epoxidivorans (96.0 % sequence similarity). Lower 16S rRNA gene sequence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 31 publications
3
53
1
Order By: Relevance
“…Also, Enterobacter , Escherichia , Klebsiella , Serratia , Bacteroides , Bacillus and Propionibacterium , which are not considered as pathogens, were also found in whitefish kidney and previously reported in freshwater fish digestive tracts in general (Austin, ). Most of the other bacteria that we found in our study are ubiquitous and can be present in soil, water or plants, for instance Methylobacterium , Paracoccus , Stenotrophomonas, Bradyrhizobium , Altererythrobacter, Croceicoccus , Kocuria or Burkholderia (Kaneko et al ., ; Lidstrom & Chistoserdova, ; Kelly et al ., ; Kwon et al ., ; Ryan et al ., ; Xu et al ., ; Bontemps et al ., ; Savini et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Also, Enterobacter , Escherichia , Klebsiella , Serratia , Bacteroides , Bacillus and Propionibacterium , which are not considered as pathogens, were also found in whitefish kidney and previously reported in freshwater fish digestive tracts in general (Austin, ). Most of the other bacteria that we found in our study are ubiquitous and can be present in soil, water or plants, for instance Methylobacterium , Paracoccus , Stenotrophomonas, Bradyrhizobium , Altererythrobacter, Croceicoccus , Kocuria or Burkholderia (Kaneko et al ., ; Lidstrom & Chistoserdova, ; Kelly et al ., ; Kwon et al ., ; Ryan et al ., ; Xu et al ., ; Bontemps et al ., ; Savini et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…The culturing also recovered some rare genera from the waters deeper than 6000 m, including Lysinibacillus, Citreicella, Altererythrobacter, Croceicoccus, Luteimonas and Winogradskyella. These genera have been previously found in deep-sea environments (Fan et al 2014;Lai et al 2009Lai et al , 2011Xu et al 2009) and some have been shown to have the ability to degrade (e.g., Lysinibacillus can degrade xylan, fomesafen and ethanethiol) (Lee et al 2010;Liang et al 2009;Wan et al 2010), indicating that they may have evolved specific strategies to survive in deep-sea environments such as the Mariana Trench. Some of the abundant groups in other culture-independent study, e.g., Epsilonproteobacteria and Cytophagia (Liu et al 2019c;Tarn et al 2016), were rare in the cultivation study reported here, indicating that the culture conditions still have many limitations.…”
Section: Highly Diverse Heterotrophic Bacteria Were Obtained From Thementioning
confidence: 97%
“…The catalytic activity of Q157E was 15 times higher than that of wild type CmGH1, most probably because that Gln157 acted as an auxiliary catalytic proton donor and glutamine had a weaker proton donating ability than glutamic acid (Brooks et al, 2001;Vocadlo et al, 2002). The bacteria C. marinus E4A9 T might prefer a weaker acid/base residue to keep an insufficient catalytic activity, which was related to the evolution divergence and was an adaptive selection for the extreme environment in deep sea (Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Croceicoccus marinus E4A9 T , a member of Erythrobacteraceae family, was isolated from a deep-sea sediment sample that was collected from the East pacific polymetallic nodule region, and was cultivated in 2216 marine broth (BD, United States) at 30 • C (Xu et al, 2009). Plasmid pSMT3 was stored in our lab and used as the vector for gene cloning and expression.…”
Section: Bacterial Strains Plasmids and Mediamentioning
confidence: 99%
See 1 more Smart Citation